Evaluating the Potential of Cultural Tourism for Community Development in Kisoro District, South Western Uganda. - Matsiko, Adam (Kabale University, 2023)
In Kisoro district, there are large communities which are impoverished, disadvantaged and living in undeveloped settlements. However, very few people benefit with the availability of cultural tourism in the area. The purpose of this study was to evaluate the potential of cultural tourism for community development in Kisoro District, south western Uganda. The specific objectives of the study were; (i) to evaluate potential cultural tourism resources, (ii) assess perceptions of local people towards cultural tourism development and (iii) to assess the contribution of cultural tourism towards the economic development of Kisoro district. Cross section design utilizing mixed methodologies was used. Both Purposive and simple random sampling techniques were used to select and obtain the respondents. Data collection methods were; questionnaires, key Informant Interviews, Observation Method. Microsoft excel was used in analysis of data collected from 85 respondents. The study found out that potential cultural tourism resources were; cultural values and life styles, architecture museums and theatres, indigenous cultural communities, art crafts and niches. Contributions of cultural are; community pride (20%), provided markets for cultural products (15% ), economic growth (09% ), demand for cultural goods (16%) and employment opportunities to local people (06). The people's perceptions on cultural tourism were; exploitation by tourists-hosts (15% ), support from the local people (22% ), aggression form of cultural people (20%), cultural differences (18%), resistance from the local communities (12%) and conflicts for local connection towards tourists (13%). There need to analyze the contributions (both positive and negative) of cultural tourism towards economic development of Kisoro district, there should be involvement of local people in decision making and be consulted on policies regarding potential cultural tourism resources and their ability to influence these decisions.